A new construction technology suitable for frame partitioned infill walls with sliding nodes and large openings: Test results. (20th October 2020) - Cheng, Xuanhao; Zou, Zuyin; Zhu, Zhanyuan; Zhai, Shuainan; Yuan, Shucheng; Mo, You; Chen, Wei; He, Junlin
Highlights: A new partitioning solution suitable for large infill frame specimens with openings. The problem of setting large openings in the partitioned infill wall was solved. The new wall exhibited a notable ductility, low damage and simple construction. Abstract: Because high damage to walls means high repair costs after an earthquake, in recent years, an increasing number of scholars have begun to focus on the vulnerability of frame-filled walls in regions with high seismicity. Traditional frame-filled walls exhibit low ductility capacities, high damage characteristics at small drift levels, and strong interactions between the frame and masonry material. Some scholars have proposed various types of partitioned infill walls. Partitioned infill walls generally have a high ductility capacity, low damage characteristics even at large drift values, and weak interactions between the frame and masonry material. Partitioned infill walls seem to have the potential to solve the problem of frame-filled wall vulnerability. However, due to the lighting and ventilation requirements of buildings, openings required for large doors and windows also need to be considered, which could seriously interfere with horizontal and vertical partitions. If this problem cannot be solved, the promotion and application of frame partitioned infill walls could be hindered. To solve this problem, this article takes a frame with a span of 5.4 m as an example and introduces the results of in-plane experiments using traditional building technology, new horizontal partitioning technology and vertical partitioning technology. Notably, many authors have suggested that the low damage to a partitioned wall is mainly related to the number of partitioned subpanels, the filling material between the wall and frame, and the setting of the sliding nodes. However, this study also found that the failure mode of the wall had a relationship with the type of frame used.